PENGARUH INDIAN OCEAN DIPOLE MODE (IODM) TERHADAP INTENSITAS HUJAN DI BENUA MARITIM INDONESIA (BMI) BARAT - Kertayasa, I Made; Sukarasa, I Ketut; Widagda, IGA; Hendrawan, I Gede (BULETIN FISIKA, 2013)
The relation of IODM with rainfall intensity of west BMI have been investigated with Fourier transform and Wavelet transform. IODM can be identified with Dipole Mode Index (DMI). This experiment used Sea Surface Temperature (SST) data from satellite Moderate Resolution Imaging Spectroradiometer (MODIS) and rainfall intensity data from satellite Tropical Rainfall Measuring Mission (TRMM). The result of Fourier transform show that the maximum period of DMI (53,5 months) and maximum period of rainfall intensity of west BMI (12 months). From that result the data is filtered 12 months and obtained correlation -0.83, that correlation mean DMI and rainfall intensity of west BMI have strong negative correlation. The result of Wavelet transform are power spectrum of DMI and rainfall intensity of west BMI. That power spectrums have been correlated, and got positive significant power spectrum correlation at period 1.5 – 1.7 year, 2.4 – 2.8 year, and 3.2 – 4.2 year and negative significant power spectrum correlation at period 3 year and 4.2 – 4.4 year.